2021
DOI: 10.1126/sciadv.abk0490
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial C1qbp promotes differentiation of effector CD8 + T cells via metabolic-epigenetic reprogramming

Abstract: Early-activated CD8 + T cells increase both aerobic glycolysis and mitochondrial oxidative phosphorylation (OXPHOS). However, whether and how the augmentation of OXPHOS regulates differentiation of effector CD8 + T cell remains unclear. Here, we found that C1qbp was intrinsically required for such differentiation in antiviral and antitumor immune responses. Activated C1qbp-deficient CD8 + T cells failed to increase mitochondrial respiratory capacities, resulting in diminished acetyl-coenzyme A as well as eleva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(15 citation statements)
references
References 54 publications
2
13
0
Order By: Relevance
“…One of these proteins, the complement component 1q subcomponent binding protein (C1qbp), was also identified as an interacting partner using pull down assays, an interaction that was validated by Western blot (table S5). C1qbp, also known as p32, gC1qR, or HABP1, is a multifunctional and multicompartmental protein mostly localized in the mitochondrial matrix but also present at the cell surface, cytosol, and nucleus ( 19, 20 ). C1qbp is an evolutionarily conserved protein that can interact with a diverse array of mitochondrial and cellular, plasma, and microbial proteins ( 20 ).…”
Section: Mainmentioning
confidence: 99%
See 2 more Smart Citations
“…One of these proteins, the complement component 1q subcomponent binding protein (C1qbp), was also identified as an interacting partner using pull down assays, an interaction that was validated by Western blot (table S5). C1qbp, also known as p32, gC1qR, or HABP1, is a multifunctional and multicompartmental protein mostly localized in the mitochondrial matrix but also present at the cell surface, cytosol, and nucleus ( 19, 20 ). C1qbp is an evolutionarily conserved protein that can interact with a diverse array of mitochondrial and cellular, plasma, and microbial proteins ( 20 ).…”
Section: Mainmentioning
confidence: 99%
“…C1qbp, also known as p32, gC1qR, or HABP1, is a multifunctional and multicompartmental protein mostly localized in the mitochondrial matrix but also present at the cell surface, cytosol, and nucleus ( 19, 20 ). C1qbp is an evolutionarily conserved protein that can interact with a diverse array of mitochondrial and cellular, plasma, and microbial proteins ( 20 ). C1qbp regulates cellular energy metabolism through modulation of mitochondrial translation or through protein-protein interactions ( 21, 22 ).…”
Section: Mainmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, it is evident that mitochondrial function not only affects tumor onset, progression and distant metastasis but also controls immune cells’ maturation, differentiation, and long-term maintenance. A body of literature indicates that C1QBP plays a vital role in mitochondrial-dependent metabolic flexibility of critical immune cells of the immune systems ( Gotoh et al, 2018 ; Zhai et al, 2021 ; Tian et al, 2022 ).…”
Section: Complement C1q Binding Protein Regulates Immune Cells Matura...mentioning
confidence: 99%
“…Moreover, it binds with the pre-mRNA splicing factor (SF2/ASF) in the nucleus, which controls RNA splicing by sequestering an essential RNA splicing factor into an inhibitory complex ( Petersen-Mahrt et al, 1999 ). However, increasing evidence has demonstrated that C1QBP predominantly resides in the mitochondria through its 33-residue N-terminal mitochondria-targeting signal (MTS) sequence and is essential for embryonic development, which is dependent on mitochondrial translation and OXPHOS ( Muta et al, 1997 ; Fogal et al, 2010 ; Yagi et al, 2012 ; Zhai et al, 2021 ). It has been reported that C1qbp deletion induces embryos’ mid-gestation lethality and triggers severe dysfunction of the mitochondrial respiratory chain due to failure of mitochondrial protein synthesis.…”
Section: Introductionmentioning
confidence: 99%